Determinan Keputusan Pembelian dalam Bisnis Coffee Shop - Sherly Hesti Erawati; Marcellino Dwi Rahmanda Agasi; Tachjuddin Tachjuddin (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to determine the effect of Store Atmosphere and Service Quality on consumer purchasing decisions in the coffee shop business. This type of research is quantitative causality to examine the relationship between variables that arise symmetrically without paying attention to the influence of another variable. The sample of this research is coffee shop visitors as many as 90 respondents. Sampling uses a sampling technique with the Accidental Sampling method. Data analysis used validity, reliability, classical assumptions, multiple linear analysis and hypothesis testing. Researchers have studied and proven that the determinants of store atmosphere and service quality in the Coffee Shop business have a positive effect on purchasing decisions. This can be interpreted, the more attractive the atmosphere of the store or the exterior and interior and the increasing quality of service based on reliability and empathy can have a positive and significant influence on purchasing decisions.Afiani, D. (2019). Pengaruh Suasana Toko Terhadap Keputusan Pembelian Pada Toko Stars. Jurnal Pendidikan Tata Niaga (JPTN), 07(03), 522-525. Amrullah, Siburian, P. S., & ZA, S. Z. (2016). Pengaruh Kualitas Produk Dan Kualitas Layanan Terhadap Keputusan Pembelian Sepeda Motor Honda. Jurnal Ekonomi dan Manajemen, 13(2), 99-118. Anderson, S., & Sin, L. G. (2020). The Influence of Store Atmosphere on Purchasing Decisions and Customer Satisfaction: A Case Study at the Pacific Restaurant, Blitar. Journal of The Community Development in Asia, 3(3), 70-78. Aryandi, J., & Onsardi. (2020). Pengaruh Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Konsumen Pada Cafe Wareg Bengkulu. Jurnal Manajemen Modal Insani Dan Bisnis (JMMIB), Vol. 1(No. 1), 117-127. Hariyanto. (2019). Riset TOFFIN: Bisnis Kedai Kopi Makin Menggeliat di 2019 Retrieved 10 Agustus, 2021, from https://www.industry.co.id/read/58786/riset-toffin-bisnis-kedai-kopi-makin-menggeliat-di-2019Kurniawan, D. (2019). Kedai Kopi di Indonesia Hampir Mencapai 3.000 Gerai Retrieved 10 Agustus, 2021, from https://voi.id/berita/925/kedai-kopi-di-indonesia-hampir-mencapai-3-000-geraiMarlius, D. (2017). Keputusan Pembelian Berdasarkan Faktor Psikologis Dan Bauran Pemasaran Pt. Intercom Mobilindo Padang. Jurnal Pundi, 01(01), 57-66. Nasution, M. I., Fahmi, M., Jufrizen, J., Muslih, M., & Prayogi, M. A. (2020). The Quality of Small and Medium Enterprises Performance Using the Structural Equation Model-Part Least Square (SEM-PLS). Journal of Physics: Conference Series, 1477(2020), 1–7.Peter, J. P., & Olson, J. C. (2010). Consumer Behavior & Marketing Strategy Solikatun, Kartono, D. T., & Demartoto, A. (2015). Perilaku Konsumsi Kopi Sebagai Budaya Masyarakat Konsumsi: Studi Fenomenologi Pada Peminum Kopi Di Kedai Kopi Kota Semarang. Jurnal Analisa Sosiologi, 4(1), 60 –74. Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, dan R & D. Bandung: Alphabeta.Sukma, E. A., Fauzi, A., & Yaningwati, F. (2012). Suasana Toko dalam Menciptakan Emosi dan Pengaruhnya terhadap Keputusan Pembelian. Profit, 6(1), 60-87. Tjiptono, F. (2014). Pemasaran Jasa: Prinsip, Penerapan, dan Penelitian ini berfokus pada konsep, teori, aplikasi, dan riset di bidang pemasaran jasa (service marketing) (Cetakan pertama ed.). Surakarta: Andi Offset.Utami, W. T., & Yuliawati. (2020). Faktor Sosial, Pribadi Dan Psikologis Yang Mempengaruhi Keputusan Pembelian Minuman Kopi Di Kampoeng Kopi Banaran. AGRILAN : Jurnal 132 Agribisnis Kepulauan, Volume 8 (No. 2), 131-148.